Hubungan Kualitas Pelayanan Kesehatan dengan Tingkat Kepuasan Pasien di Puskesmas Melati Kabupaten Kapuas - Khaira Amini; Jum’ah Jum’ah; Azhari, Fahrin (Jurnal Siti Rufaidah, 2025)
Quality healthcare services are a crucial factor in improving patient satisfaction and are an indicator of the success of healthcare facilities. Based on the results of the 2024 Semester I Public Satisfaction Survey (January–June), Melati Community Health Center (Puskesmas Melati) achieved a satisfaction score of 80.84%. This score indicates good service quality, but remains below the established Minimum Service Standards (SPM), which is more than 90%. This condition requires a comprehensive evaluation of the relationship between service quality and patient satisfaction levels. Therefore, this study was conducted to determine the extent to which healthcare service quality influences patient satisfaction at Melati Community Health Center, Kapuas Regency. The study used a quantitative approach with a cross-sectional design. The study population was all 985 patients who visited Melati Community Health Center, Kapuas Regency in January 2025. The study sample was determined at 285 respondents through random sampling techniques to obtain representative data. The research instrument was a structured questionnaire that assessed the dimensions of service quality and patient satisfaction levels. Data analysis was performed using the Spearman Rank test to determine the relationship between variables. The results of the study showed that the majority of patients rated the quality of health services as very good (26.6%). In addition, the majority of patients also expressed satisfaction with the health services provided (30.9%). Statistical tests proved a significant relationship between service quality and patient satisfaction levels (p = 0.000 < 0.05) with a correlation coefficient of 0.693. This means there is a strong and positive relationship, so that the better the service quality, the higher the patient satisfaction. The conclusion of this study emphasizes the importance of improving the quality of health services at the Melati Community Health Center. Aspects that need attention are improving physical appearance (tangibles), simplifying service procedures, and strengthening the competence and empathy of staff.